Social control in precolonial Igboland of Nigeria - Onyeozili, Emmanuel C. (African journal of criminology and justice studies, 2012)
This study is a descriptive investigation of the traditional system of social control and order maintenance in the Igbo nation of Nigeria in Africa. It discusses how the Igbo employed customary standards of conduct and negative sanctions for breach of norms to control its people prior to the advent of the Europeans, colonization, and prisons. Employing ethnographic methodology, the paper describes what constitutes serious deviance and the stringent penalties imposed for their contravention in pre-colonial Igboland. Specifically, the Igbo employed the services of council of elders, age-grade associations, title-making associations, oracles, “Dibia” fraternities (medicine men), secret societies, the myth of reincarnation and non-transmigration, and the invocation of spirits of the ancestors (“mmanwu” and ancestral worship) to preserve collective conscience. Finally, the paper suggests a re-evaluation by current government in Igbo nation to determine a possibility of co-opting certain elements of pre-colonial systems into the 21st century social control in Igbo states.